MANAJEMEN RISIKO PEMBIAYAAN KEPEMILIKAN RUMAH (KPR) GRIYA iB HASANAH PADA BANK BNI SYARIAH - Syepry Maulana Husain; Ari Asmawati (Jurnal Informatika, 2017)
Â Bank BNI Syariah is one of the Islamic Financial Institutions, which plays an important role in the storage and distribution of funds to communities in need. In the finance portfolio Ownership (KPR) Bank BNI Syariah must be selective in assessing the feasibility filed by the debtor. This assessment is done so that the bank BNI Syariah avoid risks or losses can not be a return to lending. Thus the conduct of credit or bank financing BNI Syariah must make an assessment based on the procedure or crediting mechanisms and internal control in order to avoid bad credit. The results of this study indicate, to anticipate emerging risks on mortgage products IB Griya Hasanah, BNI Syariah has application in anticipation of the risk occurring particularly the risk of credit or financing. Bank BNI Syariah apply multiple ways based on the regulations of Bank Indonesia No. 13/23 / PBI / 2011 regarding the implementation of Risk Management in Islamic banks and Islamic business units, among which the risk assessment process with the first step taken is to identify risk, then the risk assessment by PBI using the scoring method is based on historical data of customers and uses analytics 5C character (character or personality), capacity (ability), capital (capital), collateral (collateral), and the condition of economic afterwards risk monitoring and measures The latter is a risk control.